INVESTIGATING LEVELS, FACTORS, AND COPING STRATEGIES OF FOREIGN LANGUAGE SPEAKING ANXIETY AMONG EFL PRE-SERVICE TEACHERS - M. Rafli, - (2023)
Demonstrating proficiency in speaking is a critical side for EFL pre-service teachers during their teaching practicum, as it establishes themselves as knowledgeable and competent teachers. Speaking is essential for responsibilities such as imparting instructions and explaining concepts. Any anxiety about speaking English among EFL pre-service teachers can hinder the effectiveness of their instruction, thereby potentially impacting the learning outcomes of their students. This study investigated the level of foreign language speaking anxiety among pre-service teachers, as well as the factors contributed to the foreign language speaking anxiety and the coping strategies used to alleviate it during the teaching practicum. Using a method of purposive sampling, nine EFL pre-service instructors were selected as participants. The English Speaking Anxiety (ESA) scale, adapted from Kralova & Tirpakova (2019), an open-ended questionnaire adopted from Marzec-Stawiarska (2019) and Karakaya (2011), and semi-structured interviews were used as research instruments in this qualitative case study. The findings revealed that the majority of EFL pre-service teachers' foreign language speaking anxiety levels fell within the moderate level. In addition, the study identified four major themes contributing to their foreign language speaking anxiety, including personal factors, classroom factors, student factors, and teaching supervisors' factors. To cope with foreign language speaking anxiety, pre-service teachers employed a variety of personal, professional, social, and institutional coping strategies.